THE EFFECT OF LIFESTYLE ON THE INCIDENCE OF HYPERTENSION IN CAMPUREJO VILLAGE, BOJONEGORO REGENCY BASED ON LAWRENCE W. GREEN'S THEORY - Bintang Junia Ningsih; Sri Mulyani; Siti Patonah; Ahmad Maftukhin; Rahmawati (PT. Radja Intercontinental Publishing, 2026)
Hypertension is a non-communicable disease that continues to increase and is influenced by various lifestyle factors such as physical activity, diet, smoking, coffee consumption, and stress levels. This study aims to analyze the influence of lifestyle on the incidence of hypertension in the community of Campurejo Village, Bojonegoro Regency based on the theory of Lawrence W. Green. The study used a quantitative analytical design with a cross-sectional approach. The study population was 2,062 residents aged 30–50 years with a sample of 92 respondents selected using a random sampling technique. Data were collected through a lifestyle questionnaire, the DASS instrument for stress levels, and blood pressure measurements using a digital sphygmomanometer. Data analysis was performed using binary logistic regression. The results showed that diet (p=0.002), smoking habits (p=0.007), and stress levels (p=0.000) significantly influenced the incidence of hypertension, while physical activity (p=0.684) and coffee consumption (p=0.318) did not significantly influence. Unhealthy diet is the most dominant factor that increases the risk of hypertension. The conclusion of this study is that lifestyle has an important role in the incidence of hypertension, especially diet, smoking habits, and stress levels, so that promotive and preventive efforts based on public health behavior are needed.